Assessment of the Influence of Citrate Concentration on the International Normalized Ratio (INR) Determined with Twelve Reagent-instrument Combinations - Chantarangkul, Veena; Tripodi, Armando; Clerici, Marigrazia; Negri, Barbara; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 1998)
Citrate concentration is one of the variables that can affect coagulation tests. However, few studies have so far been performed to assess the magnitude of this effect on coagulation tests in general and PT in particular. The aim of this study was to assess the extent of influence of citrate concentration on the PT test with results expressed as INR. Twelve reagent-instrument combinations (systems) were calibrated vs. the Reference Preparation BCT/441 using plasmas collected in either 105 mM or 129 mM citrate from normals and anticoagulated patients (OAT). PTs for plasmas collected in 129 mM citrate were longer than those collected in 105 mM both for normals and patients on OAT, but the ratios (patient-to-normal clotting times) for the two citrate concentrations were significantly different in many instances, implying that the International Sensitivity Index (ISI) is also different. ISIs for calibrations with plasmas collected in 105 mM were greater (up to 10%) than those with plasmas collected in 129 mM citrate. When PT ratios were transformed into INR using crossover ISIs (i.e., plasmas collected in 105 mM and ISI determined with plasmas collected in 129 mM citrate, or vice versa) we found that an INR of 4.5 could be up to 20% apart from the value that would have been obtained if the appropriate ISI was used. Moreover, if the ISI determined with the manual technique was used to convert PTs obtained with a particular instrument into INR, the effect of citrate concentration was even greater (INR difference up to 64%). Should these observations be valid for other systems, they might provide additional explanations for the frequent reports which document discrepancies in the INR determined with different systems to which incorrect ISI might have been applied. World-wide consensus on a single citrate concentration to collect patients’ as well as lyophilized plasmas to be used in External Quality Assessment Schemes and for local system calibration is therefore urgently needed.